Langkawiana maculata gen. et sp. n. from Malaysia and its systematic position in the tribe Robsonomyiini (Diptera: Keroplatidae) - Ševčík, Jan (Zootaxa, 2009)
A new genus and species of Keroplatidae (Diptera), Langkawiana maculata gen. et sp.n., is described and its systematic position is discussed. The description is based on a male collected at Langkawi Island (Malaysia). Diagnostic characters of the new genus are as follows: the absence of ocelli, membraneous area around cerebral sclerite continues behind compound eyes, both orbital sclerite and frons well developed, short palpomeres, wings with dark bands, relatively long radio-median fusion, tibial trichia arranged in regular rows, reduced spurs on mid and hind tibia, and details on male terminalia. A new phylogenetic analysis of the tribe Robsonomyiini is proposed and a key to genera is presented.